Faktor Penyebab Meningkatnya Minat Kunjung Pemustaka ke Gedung Pusat Informasi dan Perpustakaan Universitas Negeri Padang - Asyifa, Ilma; Ardoni, Ardoni (Departemen Informasi Perpustakaan dan Kearasipan, 2024)
This research aims to describe the causes of increased interest in visiting the Information Centre and Library of Universitas Negeri Padang based on internal factors and external factors that influence a person's interest in visiting. This type of research is qualitative research using descriptive method. Based on the results of the research conducted, it shows that the factors that cause increased interest in visiting the library to the Information Centre and Library of Universitas Negeri Padang are based on two factors, namely. (1) Internal factors: the physical attractiveness of the building and complete facilities are also the main drivers in increasing the interest in visiting the library. Social media and the influence of friends also motivate visits, although there are complaints about air conditioning temperature, limited lockers and lift access. (2) External factors: the availability of collections and the quality of study spaces, also play an important role in increasing interest in visiting the library. This study recommends improving the collection and creating an environment that supports social interaction to increase interest in visiting